2022
DOI: 10.1128/mbio.00219-22
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Melanin Biosynthesis Pathway as Source for Fungal Toxins

Abstract: Mycotoxins are a major threat for human health. Food safety control relies on the identification of the toxins or the detection of the expression of the respective genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 72 publications
0
30
0
Order By: Relevance
“…In some melanized fungi, Ywa1 serves as precursor and can be hydrolyzed to 1,3,6,8-tetrahydroxynaphthalen (T4HN). T4HN may then be converted to 1,8-dihydroxynaphthalene (1,8-DHN) melanin through the DHN pathway 32 . However, Lim et al 28 concluded that P. variotii does not produce true melanin as the pigmentation was maintained when the DHN-melanin pathway was inhibited.…”
Section: Resultsmentioning
confidence: 99%
“…In some melanized fungi, Ywa1 serves as precursor and can be hydrolyzed to 1,3,6,8-tetrahydroxynaphthalen (T4HN). T4HN may then be converted to 1,8-dihydroxynaphthalene (1,8-DHN) melanin through the DHN pathway 32 . However, Lim et al 28 concluded that P. variotii does not produce true melanin as the pigmentation was maintained when the DHN-melanin pathway was inhibited.…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for this increase were unclear given that regulation of secondary metabolite pathways are complex. It has recently been shown in Alternaria alternata that the biosynthetic pathway for altertoxin production utilises many of the enzymes of the DHN-melanin pathway, indicating this pathway as a source for fungal toxin production 27 . Despite the increased roquefortine C levels observed in certain DHN-melanin gene deletants, it is important to note that levels still remained relatively low and of the same overall magnitude of the 74-88 production strain.…”
Section: Discussionmentioning
confidence: 99%
“…However, they occur at su ciently low enough concentrations in blue cheeses that they have been deemed a negligible risk to human health 25,26 . Though it has recently been reported that the melanin biosynthetic pathway itself can lead to production of certain mycotoxins 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Although thorough investigations on the biosynthesis of the BjF-derived toxins were not performed, some details are still known: The biosynthesis seems to be strongly correlated with the melanin pathway with 1,8-dihydroxynaphthalene ( 45 ) and 1,3,8-trihydroxynaphthalene ( 46 ) as possible intermediates. ,, Actually, the feeding of 45 to Annulohypoxylon sp. led to an up to 3-fold production of daldinones B and H .…”
Section: Biosynthesis Of Benzo[j]fluoranthene-derived Natural Productsmentioning
confidence: 99%